The Limits to Moral Erosion in Markets: Social Norms and the Replacement Excuse - Björn Bartling; Yagiz Özdemir (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper studies the impact of a key feature of competitive markets on moral behavior: the possibility that a competitor will step in and conclude the deal if a conscientious market actor forgoes a profitable business opportunity for ethical reasons. We study experimentally whether people employ the argument “if I don't do it, someone else will” to justify taking a narrowly self-interested action. Our data reveal a clear pattern. Subjects do not employ the “replacement excuse” if a social norm exists that classifies the selfish action as immoral. But if no social norm exists, subjects are more inclined to take a selfish action in situations where another subject can otherwise take it. By demonstrating the importance of social norms of moral behavior for limiting the power of the replacement excuse, our paper informs the long-standing debate on the effect of markets on morals.
Keywords: C92; D02; D63; 330; replacement excuse; social norms; moral behavior; competition; markets; utilitarianism; deontological ethics